2019
DOI: 10.1177/0734371x19850886
|View full text |Cite
|
Sign up to set email alerts
|

Retirement and the Sectors: Do Private and Public Personnel Differ in Their Retirement Decision?

Abstract: Retirement is a field of growing interest in both the public and the private sectors. Given the aging workforce in Western countries, understanding the factors that contribute to an employee’s decision to retire is an area of increasing interest to political, economic, social, and organizational scholars. Most retirement studies concentrate on a narrow set of factors, examining their impact on retirement in isolation of the broader context. Drawing from public management theory, and based on theories of person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 87 publications
(130 reference statements)
0
2
0
Order By: Relevance
“…Private sector employees demonstrated higher autonomy and relatedness satisfaction, while public sector employees demonstrated higher autonomy frustration. Based on previous research (Baum, Mooney, Robinson, & Solnet, 2020 ; Levi, Vashdi, & Vigoda‐Gadot, 2020 ), the authors hypothesized that public sector employees would demonstrate lower scores on basic psychological needs' satisfaction. Moreover, some studies indicated that the quality of interpersonal relationships was better in the private sector than in the public (Szostek, 2020 ), while emotional support during the COVID‐19 pandemic were also associated with less stress and burnout (Afulani et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Private sector employees demonstrated higher autonomy and relatedness satisfaction, while public sector employees demonstrated higher autonomy frustration. Based on previous research (Baum, Mooney, Robinson, & Solnet, 2020 ; Levi, Vashdi, & Vigoda‐Gadot, 2020 ), the authors hypothesized that public sector employees would demonstrate lower scores on basic psychological needs' satisfaction. Moreover, some studies indicated that the quality of interpersonal relationships was better in the private sector than in the public (Szostek, 2020 ), while emotional support during the COVID‐19 pandemic were also associated with less stress and burnout (Afulani et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…region of origin) factors in employee retirement decisions (e.g. Ali and Frank, 2019;Lei, 2019;Levi et al, 2019;Nguyen and Rozsa, 2019). However, we have little understanding of whether and how employees' stable psychological factors may relate to their retirement investment decisions (Dulebohn et al, 2009;Huselid, 2011;Xavier, 2014).…”
mentioning
confidence: 99%